Ni2P promotes the hydrogenation activity of naphthalene on wrinkled silica nanoparticles with tunable hierarchical pore sizes in a large range. Issue 33 (8th August 2019) - Hu, Di; Duan, Aijun; Xu, Chunming; Zheng, Peng; Li, Yuyang; Xiao, Chengkun; Liu, Cong; Meng, Qian; Li, Huiping
Abstract : Herein, a series of wrinkled silica nanoparticles with hierarchical pores (HPWSNs) were successfully prepared by dual-templating, of which the Ni2 P/HPWSNs-0.13 catalyst with the smallest Ni2 P particles exhibited the highest naphthalene hydrogenation activity. Abstract : Herein, a series of wrinkled silica nanoparticles with hierarchical pore (HPWSNs) supports were successfully prepared by dual-templating, and the special wrinkle pore structures in the monodisperse HPWSN samples were found to be beneficial for reducing the diffusion resistance of macromolecular aromatic compounds and achieving high dispersion of Ni2 P active phases. Moreover, the distance between wrinkles in silica nanoparticles could be easily tuned by changing the ratios of SDS/CTAB through charge-reversed interactions. It was found that the Ni2 P/HPWSNs-0.13 catalyst with smallest Ni2 P particles had highest surface area and biggest pore volume. Furthermore, the Ni2 P/HPWSNs-0.13 catalyst exhibited highest naphthalene hydrogenation conversion as well as 99.9% selectivity to decalin at 320 °C. To correlate the internal relationship between the macroscopic catalytic performance in the experiment and the atomic chemistry in the microscopic point of view, DFT calculations were performed, and the results showed that stronger adsorptions of naphthalene and tetralin occurred over the Ni(2) sites than those over the Ni(1) sites. Therefore, it can be concluded that the superior catalytic activity of the Ni2 P/HPWSNs-0.13 catalyst is due to the synergistic effect of the center-radical framework structure and the small sizes of Ni2 P particles, which are conducive to exposing more Ni(2) sites on the support surface, thus inducing more H for the naphthalene hydrogenation reaction.